Rupture of extensor tendons due to osteoarthritis of the distal radio-ulnar joint. - Carr, A; Burge, P (1992)
Extensor tendons ruptured in 12 patients as a result of osteoarthritis of the distal radio-ulnar joint. Rupture occurred without warning in ten cases and was sequential in five. Perforation of the dorsal capsule of the distal radio-ulnar joint, allowing contact between the roughened ulnar head and extensor tendons, was present in every case. The capsular performation was demonstrated by arthrography, which may be used to identify patients who are at risk of extensor tendon rupture. Loss of independent extension of the little finger is a valuable clinical sign because rupture of extensor digiti minimi may be masked by a powerful contribution from the extensor tendon of the ring finger.